قاعدة العبرة بعموم اللفظ لا بخصوص السبب ونماذج من تطبيقاتها الفقهية - داود، محمود علي Dawood, Mahmoud Ali (جامعة كركوك, 2015)
الحمدلله وكفى والصلاة والسلام على سيدنا محمد المصطفى وعلى آله وأصحابه الشرفا، وبعد: فقاعدة: (العبرة بعموم اللفظ لا بخصوص السبب)، التي بنيت على أساسها الكثير من أحكام الشريعة وفي شتى أبواب الفقه، وكانت سببا من أسباب اختلاف الفقهاء في كثير من المسائل فحاولت أن أسلط الضوء على تلك القاعدة، ببيان ماهيتها ومعناها وما تنطبق عليه وكيف استخرجت الاحكام الفقهية بناءا عليها، فكان البحث بعنوان: (قاعدة العبرة بعموم اللفظ ونماذج من تطبيقاتها الفقهية)، ولا أدعي أن الموضوع لم يدرس سابقا، بل أستطيع القول جازما أنه قد كتب فيه، لكني حاولت أن يكون البحث بأسلوب مختلف من خلال الاقتصار على كتب المتقدمين من العلماء، وأن يكون البحث بأسلوب مختلف من خلال الاقتصار على كتب المتقدمين من العلماء، وأن يكون ترتيب مطالبة ومباحثة وفق الترتيب الذي تناوله اغلب الأصوليين لهذا الموضوع في كتبهم، وما نقل من آراءهم في بناء واستنباط قاعدة العبرة بعموم اللفظ لا بخصوص السبب، فجاء البحث على ثلاثة مطالب: الأول: التعريف بقاعدة (العبرة بعموم اللفظ، لا بخصوص السبب)، والثاني: تحرير محل النزاع وكيفية بناء الأصوليين لقاعدة (العبرة بعموم اللفظ)، والثالث: نماذج لتطبيقات فقهية متعلقة بقاعدة (العبرة بعموم اللفظ)، ثم خاتمة في بيان النتائج التي تم التوصل إليها من خلال البحث. ويبقى ما كتبته في هذا البحث جهدا بشريا متواضعا ومحلا للنقص وورود الخطأ، فما كان منه صوابا فمن الله وحده وله الحمد أولا وآخرا، وما كان من خطأ فمني ومن الشيطان واستغفر الله على ذلك.
Praise be to Allah, and enough is enough and peace and blessings be upon the Prophet Muhammad Mustafa and his family and his companions, and after: base is: (a lesson general body of expression is not about the cause), which is built on the basis of which a lot of the provisions of the law in various sections of jurisprudence, and was the cause of the different scholars in many of the issues I tried to highlight that rule, a statement in its essence and meaning and apply it and how it was extracted jurisprudence based on them, was a research entitled: (Abra base generality pronunciation and models of applications jurisprudence). It does not pretend that the subject has not been studied previously, but I can say firmly that it has wrote it, but I tried to be a search in a different way through exclusive wrote applicants from scientists, and to be the order of demands and reasoning according to the order in which they dealt with the majority of fundamentalists this subject in their books, and the transfer of their views in the construction and development of the lesson base generality word is not about reason, He came Search on three demands: first: Definition base (lesson general body of expression, not about the cause), and the second edit dispute and how to build a fundamentalist base (lesson general body of expression), and the third: models for applications doctrinal related base (lesson generality word), then Conclusion In a statement, the results that have been reached through the search. It remains what I wrote in this research effort humanly modest and subject to the receipt of deficiency and error, what it was properly so it is Allah alone has the praise first and foremost.
Keywords: الفقه الإسلامي -- القواعد الفقهية -- قاعدة العبرة بعموم اللفظ لا بخصوص السبب